Image processing and analysis with graphs : theory and practice - Grady, Leo; Lezoray, Olivier (Digital imaging and computer vision series, 2012)
"The first book to serve as a comprehensive review of digital imaging and computer vision, this book begins with an introduction chapter to ease readers unfamiliar with concepts into following topics. The book is divided into two parts that focus on the processing of functions on graphs, graph-based image processing, and the representation and analysis of objects on graphs, graph-based image analysis. Each chapter provides a comprehensive review on a specific topic, which ranges from research challenges to industry trends, and provides numerous examples to illustrate how the proposed methods can be used in practice. A companion website is available"-- Provided by publisher